2019
DOI: 10.3389/fmicb.2019.01629
|View full text |Cite
|
Sign up to set email alerts
|

An Apple a Day: Which Bacteria Do We Eat With Organic and Conventional Apples?

Abstract: Apples are among the most consumed fruits world-wide. They represent a source of direct human exposure to bacterial communities, which is less studied. We analyzed the apple microbiome to detect differences between tissues and the impact of organic and conventional management by a combined approach of 16S rRNA gene amplicon analysis and qPCR, and visualization using fluorescence in situ hybridization and confocal laser scanning microscopy (FISH-CLSM). Each apple fruit harbors different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 54 publications
3
100
2
1
Order By: Relevance
“…Previous research revealed spatial and temporal changes in the composition of the microbiome of different portions (peel, wound, calyx-end, stem-end) of apple fruit obtained at the point of consumer purchase (supermarket) and representing fruit grown using different approaches (organic vs. conventional) [10]. Similar research was recently conducted that focused on the bacterial composition of harvested apples in different fruit tissues and the impact of organic vs. conventional management practices [14]. These studies, however, could not discern when particular components of the microbiome became established or were altered, or the impact that different postharvest processing procedures had on the composition of the microbiome.…”
Section: Introductionmentioning
confidence: 84%
“…Previous research revealed spatial and temporal changes in the composition of the microbiome of different portions (peel, wound, calyx-end, stem-end) of apple fruit obtained at the point of consumer purchase (supermarket) and representing fruit grown using different approaches (organic vs. conventional) [10]. Similar research was recently conducted that focused on the bacterial composition of harvested apples in different fruit tissues and the impact of organic vs. conventional management practices [14]. These studies, however, could not discern when particular components of the microbiome became established or were altered, or the impact that different postharvest processing procedures had on the composition of the microbiome.…”
Section: Introductionmentioning
confidence: 84%
“…The epidermis excision method also was restricted to a small surface area of the apple (approximately 1 cm 2 ) based on input thresholds dictated by the extraction kit used in these experiments, reducing the likelihood of recovering a DNA sample that was representative of the peel microbiome. This downfall could be mitigated by subsampling each apple at several key areas (equator, shoulder, stem, and calyx) [ 27 , 59 ], which would quadruple costs associated with extraction, as each subsample would require individual processing.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the relatively high abundance of microorganisms in the plant rhizosphere [ 26 ], microenvironments within the phyllosphere, specifically the carposphere, pose a significant barrier to high-quality microbiome research due to their low abundances of microorganisms, particularly on the fruit surface [ 27 ]. This is partially affected by conditions of the growing environment to which the aerial structures are exposed, including ultraviolet light exposure [ 28 ], limited nutrients and desiccation [ 29 ], and the physiological status of the plant [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Las manzanas recién cosechadas y manejadas orgánicamente albergan una microbiota más diversa y uniforme, en comparación con las convencionales; la abundancia de casi 40% de los géneros y órdenes bacterianos difirió significativamente entre las manzanas de manejo orgánico y convencional. 8 La presencia de ciertos microorganismos está definida como un indicador de contaminación fecal, pero diversos organismos no se asocian necesariamente con material fecal en alimentos tales como verduras, frutas, algunos tipos de carne, postres, pescados, mariscos (la mayoría de los cuales fueron congelados) y cereales secos; esto podría indicar que los organismos coliformes en congelados o productos secos son capaces de iniciar el crecimiento en una forma relativamente no inhibitoria.…”
Section: Mal Manejounclassified